2014
DOI: 10.1590/s0100-7203201400050002
|View full text |Cite
|
Sign up to set email alerts
|

Por que a prevalência de resultados citopatológicos do rastreamento do câncer do colo do útero pode variar significativamente entre duas regiões do Brasil?

Abstract: ResumoOBJETIVO: Analisar a prevalência dos resultados citopatológicos empregados para o rastreamento do câncer do colo do útero em relação à faixa etária da mulher e ao tempo de realização do último exame, no Rio de Janeiro e Maceió, pelo Sistema Único de Saúde. MÉTODOS: Foram analisadas as informações do Sistema de Informação do Câncer do Colo do Útero referentes aos resultados dos exames citopatológicos realizados em 2011, que totalizaram 206.550 para Rio de Janeiro e 45.243 para Maceió. RESULTADOS: No Rio d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…A similar proportion was found by Fernandes et al [23] while Longatto-Filho et al [24] reported a ratio of 8 to 1. The average age of patients with ASC-US was almost 2 years below that of the ASC-H group, and this is in line with other observations [25]. The mean parity for the ASC-US group was also lower than that of the ASC-H group, in part explained by the fact that a higher parity is correlated with a higher incidence of intraepithelial lesions [26].…”
Section: Discussionsupporting
confidence: 86%
“…A similar proportion was found by Fernandes et al [23] while Longatto-Filho et al [24] reported a ratio of 8 to 1. The average age of patients with ASC-US was almost 2 years below that of the ASC-H group, and this is in line with other observations [25]. The mean parity for the ASC-US group was also lower than that of the ASC-H group, in part explained by the fact that a higher parity is correlated with a higher incidence of intraepithelial lesions [26].…”
Section: Discussionsupporting
confidence: 86%
“…In line with this recommendation, 84.5 % of cervical cancer and precursor lesions were described in this age group. A study conducted in 2011 in two Brazilian municipalities with different socioeconomic characteristics, Rio de Janeiro in the southeast region and Maceió in the northeast region, showed that the percentage of tests in the 25–64 year age group was 78.1 and 74.7, respectively, with a predominance of younger women in Rio de Janeiro and older in Maceió [ 12 ]. Another study conducted in the state of Maranhão analysing the 139,505 cervical screenings performed during 2011 showed that 76.8 % were women aged 25–64 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the recommendations from the Brazilian Guidelines [ 11 ], this study showed that in most cases (58.8 %), women have exams at intervals of less than three years. Higher rates were observed in Maceió (68.8 %) and Rio de Janeiro (74.3 %) [ 12 ]. In another study involving women living in 13 communities located in Baixada Fluminense, on the outskirts of the state capital of Rio de Janeiro, 70.7 % of women had up-to-date screening [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas condições estão presentes quando analisamos a morbimortalidade por CCU no Brasil, as diferenças parecem resultar de hábitos e comportamentos regionais, decorrentes de um construto social e cultural. 3,4 No Brasil, a previsão para os anos de 2018 e 2019 é de 16.370 novos casos de CCU, representando a terceira neoplasia mais frequente em mulheres e, verdadeiramente, um problema de saúde pública. A maior incidência da doença está na região Norte do país e o estado do Amazonas apresenta o maior número de casos e alta taxa de mortalidade.…”
Section: Introductionunclassified